Case Report: A new therapeutic option for a rare patent ductus arteriosus child complicated with pulmonary artery aneurysm due to infectious endocarditis - Zhang, Hua-yong; Feng, Xiao-yuan; Li, Chang-jian; Zhang, Yong (Frontiers in Cardiovascular Medicine, 2025)
Patent ductus arteriosus (PDA) is one of the most common forms of congenital heart disease (CHD). Infectious endocarditis (IE) is a rare but serious complication of PDA. PDA combined with pulmonary artery aneurysm (PAA) due to IE is rare in children. In this report, we report a rare pediatric PDA case, complicated with PAA due to IE. Transcatheter closure of PDA without the surgical intervention of PAA was performed, with a favorable prognosis.